Vigorous Exercise Training Improves Reactivity of Cerebral Arterioles and Reduces Brain Injury Following Transient Focal Ischemia. (August 2014) - Arrick, Denise M.; Yang, Shu; Li, Chun; Cananzi, Sergio; Mayhan, William G.
Abstract Objective Our objective was to examine whether vigorous exercise training (VExT) could influence nitric oxide synthase (NOS)‐dependent vasodilation and transient focal ischemia‐induced brain injury. Rats were divided into sedentary (SED) or VExT groups. Materials and Methods Exercise was carried out 5 days/week for a period of 8–10 weeks. First, we measured responses of pial arterioles to an eNOS‐dependent (ADP), an nNOS‐dependent (NMDA) and a NOS‐independent (nitroglycerin) agonist in SED and VExT rats. Second, we measured infarct volume in SED and VExT rats following middle cerebral artery occlusion (MCAO). Third, we measured superoxide levels in brain tissue of SED and VExT rats under basal and stimulated conditions. Results We found that eNOS‐ and nNOS‐dependent, but not NOS‐independent vasodilation, was increased in VExT compared to SED rats, and this could be inhibited with L‐NMMA in both groups. In addition, we found that VExT reduced infarct volume following MCAO when compared to SED rats. Further, superoxide levels were similar in brain tissue from SED and VExT rats under basal and stimulated conditions. Conclusions We suggest that VExT potentiates NOS‐dependent vascular reactivity and reduces infarct volume following MCAO via a mechanism that appears to be independent of oxidative stress, but presumably related to an increase in the contribution of nitric oxide.